Application of the Exp (−φ(ζ))-expansion method for solitary wave solutions. Issue 1 (2nd January 2019) - Ayub, Kamran; Khan, M. Yaqub; Rani, Attia; Ul Hassan, Qazi Mahmood; Ahmed, Bilal; Shakeel, Muhammad
Abstract: The solution of nonlinear mathematical models has much importance and in soliton theory its worth has increased. In present article, a research has been conducted of Caudrey-Dodd-Gibbon and Pochhammer-Chree (PC) equations, to discuss physics of these equations and to attain soliton solutions. Exp ( − φ ( ζ ) ) -expansion technique is used to construct solitary wave solutions. Wave transformation is applied to convert problem in the form of ordinary differential equation. The drawn-out novel type outcomes play an essential role in the transportation of energy. It is noticed that under the study, the approach is extremely dependable and it may be prolonged to further mathematical models signified mostly in nonlinear differential equations.